PROSES KOMUNIKASI MASYARAKAT CYBER DALAM PERSPEKTIF INTERAKSI SIMBOLIK - Rohayati Rohayati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Changes in the form of communication that occurs can not be separated from the development of communication and information technology. Lots of people who use communication technology as a primary way to convey a message, consequently the message conveyed more rich meaning because the message is delivered in the form of symbols. Cyber society as a virtual society depends on the symbols in conveying the message. Symbolic interactions are used by the cyber community to convey messages. Not infrequently we find that the meaning of the symbols conveyed is interpreted differently, resulting in mutlipersepsi. This paper examines how the communication culture of cyber societies, what kind of communication patterns are used to convey messages, and how to give meaning to the symbols communicated. In addition, the author also examines the process of symbolic inteaction that takes place in cyber society. As is known that the symbolic interaction can not be separated from the communication process that occurs in cyber society.